Jupiter's auroral-related stratospheric heating and chemistry III: Abundances of C2H4, CH3C2H, C4H2 and C6H6 from Voyager-IRIS and Cassini-CIRS - Sinclair, J; Moses, J; Hue, V; Greathouse, T; Orton, G; Fletcher, L; Irwin, P (Elsevier, 2019)
We present an analysis of Voyager-1-IRIS and Cassini-CIRS spectra of Jupiter's high latitudes acquired during the spacecrafts' respective flybys in November 1979 and January 2001. We performed a forward-model analysis in order to derive the abundances of ethylene (C2H4), methylacetylene (CH3C2H), diacetylene (C4H2) and benzene (C6H6) in Jupiter's northern and southern auroral regions. We also compared these abundances to: 1) lower-latitude abundances predicted by the Moses et al. (2005) ‘Model A’ photochemical model, henceforth ‘Moses 2005A’, and 2) abundances derived at non-auroral longitudes in the same latitude band. This paper serves as an extension of Sinclair et al. (2017b), where we retrieved the vertical profiles of temperature, C2H2 and C2H6 from similar datasets. We find that an enrichment of C2H4, CH3C2H and C6H6 with respect to lower-latitude abundances is required to fit the spectra of Jupiter's northern and southern auroral regions. For example, for CIRS 0.5 cm−1 spectra of Jupiter's southern auroral region, scale factor enrichments of 6.40−1.15+1.30 and 9.60−3.67+3.98 are required with respect to the Moses 2005A vertical profiles of C2H4 and C6H6, respectively, in order to fit the spectral emission features of these species at ∼950 and ∼674 cm−1. Similarly, in order to fit the CIRS 2.5 cm−1 spectra of Jupiter's northern auroral region, scale factor enrichments of 1.60−0.21+0.37, 3.40−1.69+1.89 and 15.00−4.02+4.01 with respect to the Moses 2005A vertical profiles of C2H4, CH3C2H and C6H6 were required, respectively. Outside of Jupiter's auroral region in the same latitude bands, only upper-limit abundances of C2H4, CH3C2H and C6H6 could be determined due to the limited sensitivity of the measurements, the weaker emission features combined with cooler stratospheric temperatures (and therefore decreased thermal emission) of these regions. Nevertheless, for a subset of the observations, derived abundances of C2H4 and C6H6 in Jupiter's auroral regions were higher (by 1 σ) with respect to upper-limit abundances derived outside the auroral region in the same latitude band. This is suggestive that the influx of energetic ions and electrons from the Jovian magnetosphere and external solar-wind environment into the neutral atmosphere in Jupiter's auroral regions drives enhanced ion-related chemistry, as has also been inferred from Cassini observations of Saturn's high latitudes (Fletcher et al., 2018; Guerlet et al., 2015; Koskinen et al., 2016). We were not able to constrain the abundance of C4H2 in either Jupiter's auroral regions or non-auroral regions due to its lower (predicted) abundance and weaker emission feature. Thus, only upper-limit abundances were derived in both locations. From CIRS 2.5 cm−1 spectra, the upper limit abundance of C4H2 corresponds to a scale factor enhancement of 45.6 and 23.8 with respect to the Moses 2005A vertical profile in Jupiter's non-auroral and auroral regions.